Public Procurement in the Belt and Road Initiative - Ghossein, Tania (World Bank, Washington, DC, 2018)
China’s “Belt and Road Initiative” (BRI) includes major infrastructure investment projects – roads, ports, railways – that aim to improve connectivity along a number of transport corridors spanning 71 countries. In this paper we find that notwithstanding the large scale of the initiative, relatively little systematic data exists on the practices being followed by the different, primarily Chinese, entities that finance BRI-related contracts and how firms are being selected to execute projects. The limited available data however indicate that Chinese companies account for the majority of BRI-procurement, even in light of their high share of total infrastructure projects in developing countries. We discuss the limited publicly available evidence on the procurement of BRI projects and specific dimensions of the institutional features pertaining to public procurement regimes of BRI countries, including China, both as embedded in domestic regulations and in international agreements that countries may be part of. Finally, we discuss the efforts that BRI countries can take -individually or as part of an international agreement- to improve procurement practices for BRI projects.